A statistical evolution model of concrete damage induced by seawater corrosion - Lv, H.; Chen, J.; Lu, Chunsheng (2021)
The transmission of sulfate ions in concrete results in formation of calcium sulfoaluminate crystals due to chemical reactions. The expansion of calcium sulfoaluminate crystals is the main cause of concrete corrosion damage. In this study, ultrasonic analysis was used to detect the modulus change of concrete due to sulfate corrosion to obtain the basic law of corrosion damage evolution. An exponential growth model was developed for the internal expansion force based on the chemical reaction rate of calcium sulfoaluminate crystallization. Then, the evolution equation of the number density of microcracks was derived based on their initiation and balance conditions. Finally, a statistical model was developed for the concrete damage evolution by integrating the volume of microcracks. It is shown that the statistical evolution model can well characterize the evolution of concrete corrosion damage.